Study on material property changes of mild steel S355 caused by block loads with varying mean stress. (November 2015) - Pawliczek, R.; Prażmowski, M.
Highlights: Fatigue tests results under block load with varying mean load values are presented. Higher value of the mean load at the beginning of the block causes hardening. Hardening causes lock of the hysteresis loop for decreased mean load values. Sequence of the load within block influences on fatigue behavior of material. Abstract: The paper presents the results of research on material property and structure changes of S355 steel samples induced by fatigue of material subjected to block bending loads, with varying mean load value. In the tests, the mean load was increased and decreased in subsequent blocks, where the amplitude varies in accordance with the accepted maximum bending moment value. The changes of strains recorded during the tests show higher maximum mean strain for the case, where the mean load increases in block. Otherwise, the maximum mean strain is three times less, than before. Some hardening occurs, which affects the mechanical properties of the material. This is visible in the results of tensile tests, where ultimate strength increases for load path with increased mean load value. Metallographic examinations revealed no fatigue cracks at this level of fatigue life.